Determination of pharmaceutical active compounds in Ceyhan River, Turkey: Seasonal, spatial variations and environmental risk assessment. Issue 8 (17th November 2019) - Guzel, Evsen Yavuz; Cevik, Fatma; Daglioglu, Nebile
ABSTRACT: Pharmaceutical pollution has gained attention with the development of analytical technology. The occurrence of 91 pharmaceutically active compounds from variety of drug groups including pain killers, antimicrobials, cardiovascular drugs, hypolipidemic drugs, central nervous system drugs, and stimulants was investigated in Ceyhan River, Turkey. Pharmaceutically active compounds were examined at 9 stations, seasonally during the periods of September 2013–August 2014. For the pharmaceutically active compound analysis, solid phase extraction (SPE) method was used and measured by using liquid chromatography tandem mass spectrometry (LC-MS/MS). Highest measured pharmaceutically active compound concentration was caffeine (4880.00 ng/L). Other high concentrated pharmaceuticals were diazepam (374.00 ng/L), gabapentin (355.00 ng/L), lidocaine (48.70 ng/L), etodolac (47.35 ng/L), metoprolol (43.60 ng/L), carbamazepine (24.25 ng/L), diclofenac (17.60 ng/L), and fluconazole (15.95 ng/L). Carbamazepine and lidocaine were the most frequently detected pharmaceutics in the river water. The results of risk assessment shows that risk quotient values (RQs) is lower than 0.01, except sertraline, which means that most of the detected pharmaceutically active compounds pose no environmental risk to aquatic environment in Ceyhan River. However, it is not possible to give precise information about the effects of all detected pharmaceutically active compounds when they behave together in the aquatic environment.